Research on Nanocatalysts and Their Application in the Catalytic Reduction of Carbon Dioxide - Wang, Xinchen (Transactions on Environment, Energy and Earth Sciences, 2024)
This article mainly elaborates on four aspects: the introduction and application of nanocatalysts, the performance advantages of nanoparticles, the catalytic reduction of carbon dioxide by nanoparticles, and prospects for the future. The first paragraph introduces why nanoparticles can act as catalysts, how nanoparticles are synthesized, and their applications. The second paragraph focuses on the favorable properties of nanoparticles, including their excellent stability, environmental friendliness, ability to reduce the required activation energy, high catalytic activity, and outstanding catalytic selectivity. The third paragraph describes in detail the process of carbon dioxide being catalytically reduced by nanoparticles to produce formic acid and methane. The prospect section summarizes the solved and unsolved challenges encountered in catalytic reduction reactions, as well as the specific directions for addressing the unsolved issues. The main problems include difficulties in the molecular activation of carbon dioxide, poor product selectivity, insufficient stability of nanocatalysts, and harsh reaction conditions for nanocatalysis.
Keywords: Nanoparticles; catalysis; methane; formic acid.